2016
DOI: 10.1016/j.neurobiolaging.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

VPS35 regulates cell surface recycling and signaling of dopamine receptor D1

Abstract: Vacuolar protein sorting-associated protein 35 (VPS35) is a retromer complex component regulating membrane protein trafficking and retrieval. Mutations or dysfunction of VPS35 have been linked to Parkinson’s disease (PD), which is pathologically characterized by the loss of dopamine neurons in brain substantia nigra region. Dopamine plays a key role in regulating various brain physiological functions by binding to its receptors and triggering their endocytosis and signaling pathways. However, it is unclear whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…Previous studies have suggested that down-regulation of DAT expression reduces presynaptic membrane resorption of DA and increases neurite outgrowth (38,39). CREB phosphorylation at Ser133 is induced by the adenylate cyclase/cAMP/PKA pathway via activation of DRD1 by DA (40)(41)(42). CREB plays a critical role in the central nervous system as a nexus for intracellular signaling pathways that regulate a variety of nervous system functions (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that down-regulation of DAT expression reduces presynaptic membrane resorption of DA and increases neurite outgrowth (38,39). CREB phosphorylation at Ser133 is induced by the adenylate cyclase/cAMP/PKA pathway via activation of DRD1 by DA (40)(41)(42). CREB plays a critical role in the central nervous system as a nexus for intracellular signaling pathways that regulate a variety of nervous system functions (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism for controlling membrane expression levels, and recycling DAT and postsynaptic dopamine receptors is not fully understood. Only recently have papers reported that both DAT and DD1R endocytic recycling require intact retromer complexes (27,28). The overexpression of VPS35 could increase DD1R membrane expression levels but not total protein levels of DD1R (27), and higher striatal dopamine levels were often related to DAT dysfunction (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Since the retromer is important for the normal functioning of neurons with neurotransmitter receptors acting as cargo molecules of the retromer (25-27), we next analyzed the expression level of the striatal dopamine transporter (DAT) and dopamine D2 receptor (DD2R), which are related to dopamine transmission at the pre-and postsynapse of dopamine neuron terminals, respectively. It should be noted that DAT and the dopamine D1 receptor (DRD1) have been reported to be retromer-dependent for synapse membrane tra cking and recycling (27,28). The western blot results showed no signi cant differences in DAT and DD2R expression (Figs.…”
Section: Hplc Analysis Of Dopamine and Its Metabolites In The Striatummentioning
confidence: 91%
“…Retromer regulates the cell surface recycling of DRD1 and its downstream signalling pathway via directly binding to DRD1. The PD-linked Vps35 D620N variant does not affect retromer's affinity with DRD1, however, it fails to rescue the DRD1 recycling or associated dopamine signalling in Vps35 knockdown neurons [95]. Impaired dopaminergic neurotransmission was also observed in the Vps35 D620N knockin mouse model [96], suggesting the molecular action of retromer in PD pathogenesis.…”
Section: Impaired Trafficking Of Neuronal Receptorsmentioning
confidence: 98%